THE THREE OF DYES TO SEE METACROMATIC GRANULA - Akhmad Sudibya (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2012)
There are two stains in addition to  Neisser’s Stain to detect metachromatic granules. The two stains are Albert’s Diphtheria Stain and Loeffler’s Alkalin Methylene Blue Stain for Metachromatic Granules. They should be taught to medical students.